2023
DOI: 10.1038/s41598-023-40087-8
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and treatment of proximal femoral fractures in the elderly U.S. population

Abstract: Proximal femoral fractures are a serious complication, especially for elderly patients. Detailed epidemiological analyzes provide a valuable resource for stakeholders in the health care system in order to foresee future development possibly influenceable by adaption of therapeutic procedures and prevention strategies. This work aimed at answering the following research questions: (1) What are the incidence rates of proximal femoral fractures in the elderly U.S. population? (2) What is the preferred treatment p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…associated with higher rates of mortality and disability, [6][7][8][9] and the associated socio-medical costs are increasing. [10,11] In China, the direct healthcare costs related to hip fractures are expected to reach 15 billion dollars by 2025, nearly double compared to 2018. [12] Currently, the primary therapy for this disease is surgery, [13] but recuperation usually requires a longer length of stay (LOS) for patients.…”
Section: The Authors Have No Conflicts Of Interest To Disclosementioning
confidence: 99%
“…associated with higher rates of mortality and disability, [6][7][8][9] and the associated socio-medical costs are increasing. [10,11] In China, the direct healthcare costs related to hip fractures are expected to reach 15 billion dollars by 2025, nearly double compared to 2018. [12] Currently, the primary therapy for this disease is surgery, [13] but recuperation usually requires a longer length of stay (LOS) for patients.…”
Section: The Authors Have No Conflicts Of Interest To Disclosementioning
confidence: 99%
“…As the population ages and the frequency of hip fractures increases, these financial burdens are predicted to increase [14]. Recent literature reported that the age-adjusted incidence of proximal femoral fractures has resulted in a plateau or decline in absolute numbers since the turn of the century [2,8,15]. However, with an increase in life expectancy, and as the size of the population older than 80 years grows, the number of proximal femoral fracture patients is expected to increase, especially in countries entering super-aged societies [2,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature reported that the age-adjusted incidence of proximal femoral fractures has resulted in a plateau or decline in absolute numbers since the turn of the century [2,8,15]. However, with an increase in life expectancy, and as the size of the population older than 80 years grows, the number of proximal femoral fracture patients is expected to increase, especially in countries entering super-aged societies [2,15,16]. It is projected that the global number of hip fractures will reach 6.3 million per year by 2050 [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the aggravation of global aging, the incidence of hip fractures in the elderly is increasing year by year, and femoral neck fractures account for >50% of hip fractures (1,2). Conservative treatment of femoral neck fractures in the elderly has increased risk of complications and high mortality, which seriously affects the quality of life of patients.…”
Section: Introductionmentioning
confidence: 99%